2020
DOI: 10.1093/jas/skaa319
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between feed efficiency and puberty in Bos taurus and Bos indicus-influenced replacement beef heifers

Abstract: The objective of this experiment was to investigate the relationship between residual feed intake (RFI) and parameters associated with reproductive efficiency in growing beef heifers. One hundred and seventy-nine replacement beef heifers (Bos taurus and Bos indicus-influenced) were enrolled in a retrospective cohort design. Heifers were assigned to a 70-d feed efficiency test, and results were utilized to retrospectively classify heifers into Low (n = 51), Medium (n = 66), or High (n = 62) RFI groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Copy number on the CNVR in ASI-AFT pair was significant in Kruskal-Wallis test and their V ST was 0.887. In previous study, EIF2S1 was overlapped with CNVR specific to a high feed efficient group of Holstein [ 54 ], which suggests the contribution of the CNVR to different feed efficiency in beef cattle between Bos taurus taurus and Bos taurus indicus [ 55 , 56 ]. The muscle development related gene CTNNA1 was overlapped with indicine-specific deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Copy number on the CNVR in ASI-AFT pair was significant in Kruskal-Wallis test and their V ST was 0.887. In previous study, EIF2S1 was overlapped with CNVR specific to a high feed efficient group of Holstein [ 54 ], which suggests the contribution of the CNVR to different feed efficiency in beef cattle between Bos taurus taurus and Bos taurus indicus [ 55 , 56 ]. The muscle development related gene CTNNA1 was overlapped with indicine-specific deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Improving feed efficiency of beef cattle is a major concern for beef producers. A recent study from Canal LB, Fontes PL, Sanford CD, Mercadante VR, DiLorenzo N, Lamb GC and Oosthuizen N [57] found that heifers that efficiently utilize feed attain puberty early than less feed efficient ones. Moreover, heifers that attain puberty at a relatively younger age have the potential to conceive early in life and be more productive throughout their lifetime [58].…”
Section: Discussionmentioning
confidence: 99%
“…Proper water management is vital throughout a cow's life cycle. Nutritional balance, assessed through food component analysis and body condition scores, also influences cattle reproductive systems, as they require a balanced diet of concentrate and roughage (Canal et al, 2020). While some cattle receive minerals from government-distributed blocks, this periodic supplementation may not consistently meet their needs.…”
Section: Discussionmentioning
confidence: 99%